2021
DOI: 10.3390/ma14164640
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Trioxide Aggregate (MTA) Upregulates the Expression of DMP1 in Direct Pulp Capping in the Rat Molar

Abstract: Mineral trioxide aggregate (MTA) is an alternative endodontic material that predicts conductive or inductive calcified tissue formation from immature pulp mesenchymal stem cells (IPMSCs). The purpose of this study was to investigate whether MTA could promote reparative odontoblast differentiation via IPMSCs in the early phase of regeneration and compare with calcium hydroxide (CH). Direct pulp capping using calcium hydroxide (CH), MTA, and MTA with platelet-rich plasma (MTA + PRP) was performed on maxillary fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In addition, the healing process after direct pulp capping in rats is comparable to the healing process observed in humans. The formation of rat dentin bridge can be histologically displayed within four weeks after direct pulp capping, which is suitable for short-term evaluation [30,31]. In this investigation, the mandibular central incisor of seven-week-old SD rats were selected as the research specimen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the healing process after direct pulp capping in rats is comparable to the healing process observed in humans. The formation of rat dentin bridge can be histologically displayed within four weeks after direct pulp capping, which is suitable for short-term evaluation [30,31]. In this investigation, the mandibular central incisor of seven-week-old SD rats were selected as the research specimen.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to morphology, there was a statistically signi cant difference between MTA, MTA + i-PRF, BBG and BBG + i-PRF, while there was no tubular newly formed bridge found. For MTA and BBG group, the high number of samples was amorphous with percent 86.67 and 75.0% respectively, the authors reported that the amorphous areas in calci ed bridge were characterized as precipitations of coarse calcium granulations, forming a super cial granular zone, which is associated with the initial synthesis and deposition of disorganised dentin matrix [15] , one of the characteristics of a bioactive material is its ability to form an apatite-like layer on its surface when it comes in contact with physiologic uids in vivo [19] or with simulated body uids Indeed, the inadequacy for true regeneration in mammals has been attributed partially to the absence of blastema formation at the site of injury (reprogramming of terminally differentiated stem cells) [20,21] and partially to the rapid bro-proliferative response that accompanies chronic in ammation and wound healing. [22] While mixed (tubular and amorphous) was high in MTA + i-PRF (85.71%) and BBG + i-PRF (100%), despite of the external layer is irregular and atubular, but the internal one exhibits the dentinal characteristics with irregular and randomly distributed tubules.…”
Section: Discussionmentioning
confidence: 99%
“…The antibody-localized antigen (ALA) was then detected by peroxidase activation of 3, 3′-diaminobenzidine for 10 min to give it brownish discoloration. (31) The area percentage (% area) was detected by a special microscope (Leica Q Win V3).…”
Section: Immunohistochemical Examination Tgf-β1 Examinationmentioning
confidence: 99%